2022
DOI: 10.1038/s41598-022-18871-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and prognostic factors in patients with refractory metastatic colorectal cancer treated with trifluridine/tipiracil plus bevacizumab in a real-world setting

Abstract: We evaluated the efficacy and safety of trifluridine/tipiracil (TAS-102) plus bevacizumab in treating refractory metastatic colorectal cancer (mCRC) in a retrospective, observational study. Patients refractory or intolerant to standard therapies received TAS-102 (30–35 mg/m2 twice daily on days 1–5 and days 8–12 every 28 days) plus bevacizumab 5 mg/kg on days 1 and 15. Clinical and pathological characteristics, overall response rate (ORR), disease control rate (DCR), overall survival (OS) and progression-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The main types of identified articles leading to exclusion were reviews, guidelines, and editorials. Ten series for potential inclusion in the meta-analysis were identified [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. After evaluation, two of the series were excluded, as they contained, based on the authors, similar centers and dates of study performance, potentially overlapping patients [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main types of identified articles leading to exclusion were reviews, guidelines, and editorials. Ten series for potential inclusion in the meta-analysis were identified [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. After evaluation, two of the series were excluded, as they contained, based on the authors, similar centers and dates of study performance, potentially overlapping patients [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the remaining eight series, six series were from Asia (of which five series were from Japan, where trifluridine/tipiracil was initially developed, and one series from China, Table 1 ) [ 18 , 21 , 22 , 23 , 24 , 25 ]. Two series were from European centers [ 19 , 20 ]. Dates of publication were between 2020 and 2022, and a total of 441 patients were described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study holds significant relevance for physicians in routine clinical practice for several reasons: (i) it represents the largest real-world dataset of patients treated with FTD/TPI + bevacizumab in routine practice in the Western world, 12 , 13 , 14 , 15 and (ii) it places a particular focus on distinct molecular subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab is an FDA-approved antiangiogenic agent targeting VEGF for the treatment of metastatic colorectal cancer (MCRC) ( Figure 1 ) ( Table 1 ) [ 36 ]. Studies have shown that the overall response rate and disease control rate of bevacizumab combination therapy in 35 CRC patients were 3.2% and 51.6%, respectively [ 37 ]. Aflibercept is also an antiangiogenic drug already in use.…”
Section: Vegf Signaling Pathway In Crcmentioning
confidence: 99%